Prevalence of iron deficiency anemia and beta thalassemia carriers among relatives of beta thalassemia patients in Nile Delta region, Egypt: a multicenter study - Mohamed R. El-Shanshory; Laila M. Sherief; Hoda M. Hassab; Seham M. Ragab; Sohier Yahia; Ahmed K. Mansour; Adel S. Ahmed; Said H. Abdou; Amal M. Helmy; Mona M. Watany; Ahmed M. Gad ALllah; Myriam A. Guindy; et al. (SpringerOpen, 2021)
Abstract Background Screening of β thalassemia among close relatives is more feasible in highly prevalent countries with limited resources. The purpose of this study is to determine the prevalence of β thalassemia carriers and iron deficiency anemia among relatives of β thalassemia patients in Mid Delta, Egypt. Methods This is a cross-sectional multi-center study conducted on 2118 relatives of patients with β thalassemia from different Egyptian governorates in the Mid Delta region. They were subjected to history taking with precise determination of geographic location, general examination, and the following investigations: complete blood counts, serum ferritin for those who showed microcytic hypochromic anemia, and high-performance liquid chromatography for those who were not diagnosed as iron deficiency anemia. Results The total prevalence of iron deficiency anemia among close relatives of confirmed β thalassemia patients in the Nile Delta region was 17.19%. The highest prevalence of iron deficiency anemia (45.05%) was reported in Al-Gharbia Governorate, followed by Al-Menoufia Governorate (21.67%), and the lowest prevalence was that of Al-Sharkia Governorate (4.91%). The differences were highly statistically significant (p < 0.001). β thalassemia carrier prevalence rate in the studied relatives was 35.84%, with the highest prevalence detected in Al-Sharkia Governorate (51.32%), followed by Kafr-Alsheikh and Al-Dakahilia Governorates (41.78%, 37.13%) respectively, while Al-Menoufia Governorate had the lowest prevalence rate (25.00%). These differences were also highly statistically significant (p < 0.001). Conclusion More than one-third of relatives of patients with β thalassemia are carriers of the disease, while 17.19% suffer from iron deficiency anemia. This study demonstrates the importance of tracing the high number of beta thalassemia carriers among relatives of patients with β thalassemia in Egypt.